Differences in the mechanical performance of type II glass ionomer cement modified with hydroxyapatite in terms of diametral tensile strength and compressive strength: an experimental study - Rahmitasari, Fitria; Syahrotaubiya, Adrikina; Fadhlillah, Baiq Alifa; Cevanti, Twi Agnita; Prabowo, Puguh Bayu; Fauzia, Bunga; Panjaitan, Rani Naomi Agustina (Universitas Padjadjaran, 2026)
Introduction: Glass ionomer cement (GIC) is widely used because of its chemical adhesion to tooth structure, fluoride release, and biocompatibility. However, its low tensile strength and brittleness limit its application in stress-bearing restorations. Hydroxyapatite (HA) has been investigated as a bioactive filler to improve the mechanical properties of GIC. This study aimed to analyze the differences in the mechanical performance (diametral tensile strength and compressive strength) of Type II GIC modified with hydroxyapatite. Methods: The materials used in this research were Type II GIC (Fuji IX) and pure hydroxyapatite (Sigma Aldrich's). Twenty-eight specimens were allocated into four groups for the diametral tensile strength (DTS) test, and another twenty-eight specimens for the compressive strength (CS) test (n= 7 per group): a control group (K, conventional GIC without modification) and three treatment groups modified with 1% (P1), 3% (P2), and 5% (P3) of hydroxyapatite powder. Mechanical evaluation was performed using a Universal Testing Machine (UTM) at a crosshead speed of 0.5 mm/min. Statistical analysis comprised tests of data normality and variance homogeneity, followed by one-way analysis of variance (ANOVA) and the Least Significant Difference (LSD) post hoc test (p=0.05). Results: The addition of HA altered mechanical performance in a highly concentration-dependent and stress-specific manner. The highest DTS was observed in Group P1, with a value of 9.5300 ± 4.0896 MPa, which was significantly higher than those of the control and all other groups (p<0.05). Conversely, CS was highest in Group P2 (66.7114 ± 11.8779 MPa), which was significantly higher than that of the control group (43.3614 ± 10.6778 MPa, p=0.002). Higher mass loading in Group P3 resulted in a pronounced decline in both tensile and compressive performance. Conclusion: There are differences in the mechanical performance (diametral tensile strength and compressive strength) of Type II glass ionomer cement (GIC) modified with hydroxyapatite. Hydroxyapatite integration enhances the mechanical properties of Type II GIC, with 1% HA improving DTS and 3% HA producing the highest CS.